Evaluation of Armothin and Ralex as chemical thinners for 'Sunlite' nectarines - Coetzee, Johan Hendrik (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1998.